Indications and Frequency Rate of Permanent Pacemaker Implantation in Elderly Patients - Mansoor, Talia; Durrani, Muhammad Akif; Khuwaja Khail, Roomana; Hameedullah; Aslam Awan, Zahid (Indus Journal of Bioscience Research, 2024)
Background: Permanent pacemaker has become essential for the treatment of various cardiac diseases nowadays. The process is carried out regularly at the Cardiac Catheterization Laboratory of Hayatabad Medical Complex, Peshawar. Objective: The purpose of the study was to determine the demographic details, indications, and type of permanent pacemaker implanted in elderly population. Methods: This was a single-center, prospective study conducted in at Hayatabad Medical Complex, Peshawar from March 2023 to August 2023. During these six months, a total of 218 Patients were included in the study who were regular in their visits to outpatient clinic and had given a written informed permission for participation. Those who did not give a written informed consent for participation were excluded from the study. Results: Total 218 patients with mean age of 63.4 years range (43-88) undergone Permanent Pacemaker Implantation. Of these 130 (60%) were males. The mean duration of hospital stay was 4.5 days with range (3-7 days). Sinus Node Disease (115 patients, 52.75%) was the most common indication for permanent pacemaker Implantation. Single chamber (VVIR) pacing mode (123 patients, 56.42%) was found to be the most common pacing mode. Conclusion: Permanent pacemaker implantation has been observed to be common among the elderly population, with a male majority. The most frequent reason for cardiac pacing in older people is sinus node disease, which is followed by atrioventricular block. In Pakistan, due to financial constraints, the single chamber (VVIR) pacing mode is frequently used, followed by the dual chamber (DDDR).